Role of Radiotherapy in Gestational Trophoblastic Neoplasia: A Case Report - Arie Munandar; Viona Viona (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2022)
Gestational trophoblastic neoplasia (GTN) is a placental tissues malignancy that is prone to massive bleeding. Multimodality treatment is often needed to treat GTN, such as surgery and radiotherapy. Radiotherapy has a palliative role in case of hemorrhage and/or intracranial metastases.Radiotherapy is effective in controlling bleeding by destructing malignant blood vessels by inducing endothelial damage and increasing signal transduction pathway leading to apoptosis and increasing adhesion of thrombocytes to vascular endothelia resulting fibrosis. No dose and fractionation schemes are proven more effective than others, but longer fractions scheme (>5 fractions) and BED10 > 39 Gy show no additional benefit in hemostatic control or in reduction of re-bleeding rate.Brain metastatic lesions are prone to bleeding that might need craniotomy for blood evacuation or brain decompression. WBRT can be given concurrently with chemotherapy in brain metastatic GTN cases. Higher WBRT total dose (>22 Gy) associated with higher 5-year local control rates.